PEMBUATAN MAGNET BONDED PERMANEN PrFeB DENGAN BINDER POLYESTER DAN SILICONE RUBBER - Hilda Ayu Marlina (Saintia Fisika, 2013)
Research on fabrications of bonded magnets PrFeB type MQEP 16-7 with polyester and silicone rubber binder has been done. The purpose of this study is determination of the effect of polyester and silicone rubber matrix on the mechanical and magnetic properties in the manufacture of bonded magnets PrFeB. The process of fabrications bonded magnets PrFeB made by mixing powder and magnets PrFeB respectively - each with variations binder composition (wt%) are 2, 4, 6, and 8. For each sample takes 8 grams total mass of bonded magnets PrFeB. The samples were made by using compression molding method with a sample pressure of 5 tons. Curing temperature of 150° C for samples bonded magnet with polyester binder and room temperature for samples bonded magnet with silicone rubber binder. The results showed that the best magnetic field derived from the manufacture of bonded magnets with the addition of 2% silicone rubber binder at 1156.9 G and energy product (BH)max 9.15 MGOe, with a value of 10.4 BHN Brinell hardness and compressive strength of 22.3 MPa.Keywords: Bonded magnet, PrFeB, polyester, silicone rubber, magnetic properties, mechanical properties